Derivational Affixes On The Weeknd's Songs In After Hours Album: A Morphological Study - Titi Wahyukti; Pudiyono; Dwi Heriyanto; Atik Muhimatun A; Gilang Candra Irela (Universitas Adiwangsa Jambi, 2021)
The purpose of this study was to identify the derivational affix process and to describe the type of derivation in the lyrics of The Weeknd’s songs from the After Hours album. Based on the 14 songs contained in the album, the method used to conduct this research is a qualitative method. The data is taken from the album AFTER HOURS from The Weeknd. The theory used is the basis of affix derivation and other derivatives. Based on the results of the study, there were 15 lyrics containing affix derivation and found that there were 6 prefixes and 9 suffixes.